2012
DOI: 10.1061/(asce)lm.1943-5630.0000198
|View full text |Cite
|
Sign up to set email alerts
|

Framework for Earthquake Evacuation Planning: Case Study for Montreal, Canada

Abstract: Disaster management planning in Canada is government led, and the responsibilities are divided among federal, provincial, and local levels of government. The Civil Emergency Plan of Greater Montreal (Plan de sécurité civile de l'agglomération de Montréal) describes operations and responsibilities during emergencies and provides a framework for the strategic management cycle, which includes action, coordination, and communication between various decision centers. However, evacuation planning processes have not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The high building code and sparse population has led Canadians to ignore emergency shelters in urban planning. Canada is vast and sparsely populated, with a national population density of only 3.41 per square meter, and its standard for seismic design is 7 [17,18], indicating that new buildings will not collapse under a 7-magnitude earthquake. However, research evaluating building damage in some parts of Victoria and Vancouver has shown that older neighborhoods may sustain up to 30% structural damage [19], indicating that open spaces as emergency shelters are needed because the indoor spaces are no longer safe.…”
Section: Conditions Of Canadian Sheltersmentioning
confidence: 99%
“…The high building code and sparse population has led Canadians to ignore emergency shelters in urban planning. Canada is vast and sparsely populated, with a national population density of only 3.41 per square meter, and its standard for seismic design is 7 [17,18], indicating that new buildings will not collapse under a 7-magnitude earthquake. However, research evaluating building damage in some parts of Victoria and Vancouver has shown that older neighborhoods may sustain up to 30% structural damage [19], indicating that open spaces as emergency shelters are needed because the indoor spaces are no longer safe.…”
Section: Conditions Of Canadian Sheltersmentioning
confidence: 99%
“…Data on the selected variables for each MUC were collected from its administration. Data on emergency shelters, medical centres and primary schools were taken from Tamima and Chouinard (2012). Data on Carbon oxide, Nitrogen oxide and Ozone at different air record stations within the MUC were collected from the Réseau de surveillance de la qualité de l'air of the City of Montreal.…”
Section: Data Collection and Manipulationmentioning
confidence: 99%
“…The Montreal region was affected by a major ice-storm in January 1998. During the ice-storm, several people took refuge in shelters or other suitable accommodations (with family and friends) but data on evacuation was not recorded in the aftermath of the ice-storm (Tamima and Chouinard 2012). Montreal is ranked second in Canada for seismic risks and a number of small earthquakes have occurred in the Montreal area but none was strong enough to cause any significant damage or evacuation.…”
Section: Datasetmentioning
confidence: 99%
“…The importance of evacuation studies in the aftermath of a disaster is recognized by the natural hazards researchers (Tamima and Chouinard 2012;Hasan et al 2010;Mesa-Arango et al 2013). Disasters result in displaced households and the estimation for the demand for shelters is a part of disaster preparedness studies.…”
Section: Introductionmentioning
confidence: 99%